2020
DOI: 10.3390/ma13194224
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin and Graphene Oxide Combination—New Face of a Known Drug

Abstract: Drug modification with nanomaterials is a new trend in pharmaceutical studies and shows promising results, especially considering carbon-based solutions. Graphene and its derivatives have attracted much research interest for their potential applications in biomedical areas as drug modifiers. The following work is a comprehensive study regarding the toxicity of ciprofloxacin (CIP) modified by graphene oxide (GO). The influence on the morphology, viability, cell death pathway and proliferation of T24 and 786-0 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The conjugates were found to facilitate the mineralization of BM-MSC cells resulting in the formation of clusters around the cells; the most effective nanostructured ZOL-GO conjugates being fabricated using 50 µM ZOL and GO suspension of 2.91 ng/mL [178]. Modification of ciprofloxacin ( Figure 5) with GO increased its cytotoxic potential in 786-0 (renal cancer) cells, and particularly T24 (human urinary bladder carcinoma) cells, as well as its apoptotic potential [179]. A needle-like GO nanocarrier obtained via conformational change of GO sheets using salt ions in the cell growth medium, was characterized with high surface area and satisfactory number of functional groups for DOX accumulation on the GO sheets.…”
Section: Unmodified Gomentioning
confidence: 99%
“…The conjugates were found to facilitate the mineralization of BM-MSC cells resulting in the formation of clusters around the cells; the most effective nanostructured ZOL-GO conjugates being fabricated using 50 µM ZOL and GO suspension of 2.91 ng/mL [178]. Modification of ciprofloxacin ( Figure 5) with GO increased its cytotoxic potential in 786-0 (renal cancer) cells, and particularly T24 (human urinary bladder carcinoma) cells, as well as its apoptotic potential [179]. A needle-like GO nanocarrier obtained via conformational change of GO sheets using salt ions in the cell growth medium, was characterized with high surface area and satisfactory number of functional groups for DOX accumulation on the GO sheets.…”
Section: Unmodified Gomentioning
confidence: 99%
“…To increase the impact of GO derivatives in a controlled and purposeful manner, functionalization is used, meaning the attachment of various functional groups to the structure of GO [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Introducing this into the environment containing the active substance in the form of a drug may cause it to attach to the surface of GO flakes not only physically but also by chemical adsorption [ 24 , 25 , 26 ]. Matulewicz et al [ 23 ] present the results of the morphology, viability, and proliferation of the T24 and 786-0 cells after subjecting them to GO nanoparticles. They observed that the effects of cytotoxicity are highly dependent on the dose and size of the nanomaterial, so further studies are needed to determine the optimal dose of GO for drug modification [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This medication is used to treat a variety of infectious disorders, including urinary tract, respiratory tract, and gastrointestinal tract infections, as well as skin and soft tissue infections. Furthermore, ingesting foods of animal origin in humans might result in allergic or carcinogenic responses owing to antibiotic residues [ 3 ]. However, the most severe of all the negative effects of antibiotic residues in the environment is the rise of microbial drug resistance.…”
Section: Introductionmentioning
confidence: 99%